2017
DOI: 10.1186/s12864-016-3417-4
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analysis of human norovirus NS1-2 protein highlights a multifunctional role in murine monocytes

Abstract: BackgroundThe GII.4 Sydney 2012 strain of human norovirus (HuNoV) is a pandemic strain that is responsible for the majority of norovirus outbreaks in healthcare settings. The function of the non-structural (NS)1-2 protein from HuNoV is unknown.Results In silico analysis of human norovirus NS1-2 protein showed that it shares features with the murine NS1-2 protein, including a disordered region, a transmembrane domain and H-box and NC sequence motifs. The proteins also contain caspase cleavage and phosphorylatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 74 publications
2
13
0
Order By: Relevance
“…These experiments demonstrate that Akt activation is a feature of MNV infection of RAW cells, and that Akt plays a role in maintaining glycolysis in these cells. Akt activation during MNV infection is consistent with a previous transcriptomic study of monocytes transfected with the non-structural protein NS1-2, which implicated NS1-2 in affecting PI3K-Akt signaling pathways (86). Taken together, these data are consistent with a model whereby MNV infection upregulates glycolysis via Akt signaling.…”
Section: Resultssupporting
confidence: 90%
“…These experiments demonstrate that Akt activation is a feature of MNV infection of RAW cells, and that Akt plays a role in maintaining glycolysis in these cells. Akt activation during MNV infection is consistent with a previous transcriptomic study of monocytes transfected with the non-structural protein NS1-2, which implicated NS1-2 in affecting PI3K-Akt signaling pathways (86). Taken together, these data are consistent with a model whereby MNV infection upregulates glycolysis via Akt signaling.…”
Section: Resultssupporting
confidence: 90%
“…The sequence of NS1-2 is highly divergent between different norovirus genogroups with no specific function assigned thus far. Bioinformatic analysis proposed an unstructured N-terminal region, which was confirmed biochemically [ 9 ], a central domain with potential hydrolase function [ 10 ] and a C-terminal transmembrane domain [ 9 , 63 ]. Norwalk virus NS1-2 was shown to disrupt the Golgi apparatus [ 11 ], whereas MNV NS1-2 mainly localizes to the ER [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an alignment of the p48 protein sequences from different norovirus genogroups, it was determined that the HuNoV Sydney p48 shares 42% identity with NV p48 (GI), 36% with Jena p48 (GIII), and 37% with MNV (GV) (29). Even though these proteins share a low similarity, through an in situ analysis it was determined that the HuNoV p48 protein has amino acid sequence characteristics like the MNV p48 protein that include: (1) a disordered region of proline-rich N-terminal, containing the alleged immunogenic regions for MHC-I binding, (2) a transmembrane hydrophobic domain at the C-terminal end, (3) H-box and NC sequence motifs of the permutated NlpC/P60 family of circular peptidases that adapt different enzyme capacities within the same structure, improving the stability and the reducing degradation caused by proteases, and (4) caspase cleavage and phosphorylation sites, which in eukaryotic cells are involved in the regulation of the cell cycle, apoptosis, and activation of the immune system (29). The specific function of the p48 protein of the different HuNoVs within the viral replicative cycle and its role in HuNoV pathogenesis in the host have not yet been elucidated.…”
Section: Characteristics and Functions Of Non-structural Proteins Of mentioning
confidence: 99%
“…Hence, a transcriptomic analysis determined, by expressing the HuNoV p48 protein in murine monocytes, revealed that it can interfere in many intracellular pathways, such as those involving the Jak-STAT, MAPK, p53, and PI3K-Akt signaling pathways. Additionally, HuNoV p48 has been shown to interfere with apoptosis, Toll-like receptors (TLR) signaling pathways, and the production of chemokines and cytokines (29). Thus, the p48 protein can play an important role in the HuNoV replicative cycle by participating in the development of the viral replication complex and by hampering the normal function of cellular signaling pathways, as well as, the activation of the immune response induced by the viral infection.…”
Section: Characteristics and Functions Of Non-structural Proteins Of mentioning
confidence: 99%
See 1 more Smart Citation